The Prime Minister as Fetish? Ironic Nationalism, the News Media, and the Canadian Legends Figurines - Rothenburger, Sunnie (International Journal of Canadian Studies / Revue internationale d’études canadiennes, 2010)
This article explores the public reception of the Canadian Legends, a series of toys based on Canadian historical figures. For some purchasers, the toys appear to act as nationalist fetishes, resolving a desire for a stable national identity in the face of numerous challenges to such an identity. Many media commentators, on the other hand, take an ironic stance toward the toys. This stance, while seeming to undercut the toymakers’ stated purpose of promoting nationalism, is actually part of a greater pattern in Canadian culture that uses irony to promote a more nuanced nationalism while upholding racial and gendered hierarchies within the nation.